Doxorubicin and Varlitinib Delivery by Functionalized Gold Nanoparticles Against Human Pancreatic Adenocarcinoma - Sílvia Castro Coelho; Daniel Pires Reis; Maria Carmo Pereira; Manuel A. N. Coelho (MDPI AG, 2019)
The aim of this study was to develop drug delivery nanosystems based on pegylated gold nanoparticles (PEGAuNPs) for a combination against pancreatic cancer cells. Doxorubicin and varlitinib, an anthracycline and a tyrosine kinase inhibitor respectively, were conjugated with gold nanoparticles. The systems were characterized, after synthesis, regarding their size, stability and morphology. An efficient conjugation of doxorubicin and varlitinib with PEGAuNPs was revealed. The cytotoxicity effect induced by the combination of the nanoconjugates was investigated in pancreatic cancer cell lines. Doxorubicin and varlitinib conjugated with PEGAuNPs revealed a combined effect to decrease the cell survival of the cancer line S2-013s, while reducing the drugs’ toxicity for the healthy pancreatic cells hTERT-HPNE. This study highlights the promising potential of PEGAuNPs for targeted delivery of therapeutic drugs into human cells, enhancing the antitumor growth-inhibition effect on cancer cells, and decreasing the toxicity against normal cells. In cancer therapy, the present approach based on PEGAuNP functionalization can be further explored to increase drug targeting efficiency and to reduce side effects.